Biogeography and evolution of Melanesian and South Pacific ants - Matos Maraví, Pável Fortunato (Jihočeská univerzita, 2016)
This thesis investigates the systematics, biogeography, and diversification dynamics of a large and ecologically important insect group in SE Asia and the Indo-Pacific region: the ants. This study utilizes a multidisciplinary framework to elucidate the evolutionary history of selected ant clades with the overall aim to shed light on similar ecological and evolutionary processes intervening in ant diversity.
Biogeography and evolution of Melanesian and South Pacific ants
Keywords: ants; Melanesia; taxon cycle; diversification; phylogeny; molecular systematics; ants; Melanesia; taxon cycle; diversification; phylogeny; molecular systematics